2020
DOI: 10.1039/d0se00360c
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional flower-like nickel phyllosilicates for CO2methanation: enhanced catalytic activity and high stability

Abstract: A group of MCF-derived nickel phyllosilicates were designed and synthesized by a hydrothermal method for enhanced CO2 methanation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The Ni crystal size of N/D-100-12, N/D-120-6, N/D-120-12, N/D-120-18, and N/D-140-12 is 4.6, 4.6, 4.7, 5.0, and 5.2 nm (Table 1), respectively, which can retain small Ni particles after high-temperature reduction derived from the strong metal−support interaction of Ni-phyllosilicates. 11,12 Furthermore, for the N/D-120-12-H sample prepared by the conventional hydrothermal method at 120 °C for 12 h, there is only a wide peak attributed to amorphous silica, indicating that no Ni-phyllosilicate is formed under such mild hydrothermal conditions without assistance of NH 4 F and urea (Figure S1). When the severe hydrothermal condition of 220 °C for 48 h is used, the N/D-220-48-H sample displays the typical diffraction peaks belonging to Ni-phyllosilicate (Ni 3 Si 2 O 5 (OH) 4 ) (Figure S2A), suggesting that the Ni-phyllosilicate can be formed using the conventional hydrothermal method through the reaction of biomass-based silica and nickel nitrate under severe hydrothermal conditions.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The Ni crystal size of N/D-100-12, N/D-120-6, N/D-120-12, N/D-120-18, and N/D-140-12 is 4.6, 4.6, 4.7, 5.0, and 5.2 nm (Table 1), respectively, which can retain small Ni particles after high-temperature reduction derived from the strong metal−support interaction of Ni-phyllosilicates. 11,12 Furthermore, for the N/D-120-12-H sample prepared by the conventional hydrothermal method at 120 °C for 12 h, there is only a wide peak attributed to amorphous silica, indicating that no Ni-phyllosilicate is formed under such mild hydrothermal conditions without assistance of NH 4 F and urea (Figure S1). When the severe hydrothermal condition of 220 °C for 48 h is used, the N/D-220-48-H sample displays the typical diffraction peaks belonging to Ni-phyllosilicate (Ni 3 Si 2 O 5 (OH) 4 ) (Figure S2A), suggesting that the Ni-phyllosilicate can be formed using the conventional hydrothermal method through the reaction of biomass-based silica and nickel nitrate under severe hydrothermal conditions.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…However, there are still some shortcomings for these methods, such as the complicated process, high cost, difficult large-scale production, loss of activity due to partial embedding of Ni particles or poor mass transfer, and so forth . It is reported that the Ni/SiO 2 catalyst can be achieved after the reduction of nickel phyllosilicates, which offers strong interaction between nickel and silica with fine Ni particles at high Ni content and exhibits high catalytic activity without the agglomeration of Ni particles. , Thus, construction and regulation of Ni-phyllosilicates are a promising solution to obtain a high Ni anti-sintering property for the Ni/SiO 2 catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Ni/SiO 2 -AE catalyst synthesized by the ammonia evaporation method, no phase of nickel oxide was observed, but only the phase of nickel phyllosilicate was shown, and 34.1, 36.7, and 60.5 were characteristic diffraction peaks of nickel silicate, Ni 3 Si 2 O 9 H 4 (JCPDS no. 49-1859) ( Zhang T et al, 2020 ; Chen et al, 2021 ; Zhang and Liu, 2021 ). Meanwhile, the distribution of nickel species was relatively uniform.…”
Section: Resultsmentioning
confidence: 99%
“…As we know, "nanosheet" is the typical morphology of phyllosilicates, and the SEM results provide the intuitive evidence of the successful formation of phyllosilicates. 32,33 thermal reaction process, SR can serve as the silica sacrificial template and react with the nickel salt to convert to nickel phyllosilicate with the increase of temperature (Figure 1h). Moreover, the prepared Ni-phyllosilicate catalysts exhibit high mechanical stability, which can retain the nanosheet-like morphology after ultrasonication for 20 min.…”
Section: Resultsmentioning
confidence: 99%